ChemInform Abstract: Zincation of 4, 4‐Dimethyloxazoline Using TMPZnCl·LiCl. A New Preparation of 2‐Aryloxazolines. Issue 33 (August 2015) - Haas, Diana; Hofmayer, Maximilian S.; Bresser, Tomke; Knochel, Paul
Abstract A simple, mild and efficient method for the zincation of 4, 4‐dimethyloxazoline in position 2 using TMPZnCl·LiCl is reported.